Fundamentals for Cost Estimating of Applied Software Development and Modification - Andon, P.I.; Ignatenko, P.P.; Sinitsyn, I.P.; Slabospitskaya, O.A. (PROBLEMS IN PROGRAMMING, 2018)
Keen Methods for Applied Software development and modification Cost estimating with COCOMO, WebMO and D. Cleary models are uniformly enhanced up to state tenders for Software Systems elaboration and maintenance. Generic procedure is proposed for the Methods enhanced cohe-rent use over all the stages of the tenders preparing, performing and control as well as an architecture draft for the tools of its automated support.Problems in programming 2016; 2-3: 264-273